ANALISIS PENERAPAN METODE PENETRATION TESTING PADA KEAMANAN JARINGAN WLAN (Studi Kasus: Universitas Maritim Raja Ali Haji) - Chahyadi, Ferdi; Sitompul, Afrio Triputra; Nurfalinda (Sustainable, 2023)
This test is carried out to find security holes in the Wireless Local Area Network (WLAN) network. In this paper, author simulates attacks on a WLAN network using four attack parameters: Bypassing MAC Authentication, Attacking The Infrastructure and Man In The Middle Attacks. There were four attacks carried out, and two of them were successful. Thus, it can be concluded that the Raja Ali Haji Maritime University (UMRAH) WLAN network is quite secure. Nonetheless, other offensive actions, such as infrastructure attacks or Man In the Middle Attacks, In order to ensure more security, it is necessary to add a DNS Security Extensions protocol to prevent fake DNS redirects, add a firewall to the security system and use TLS on captive portals.